Usefulness of Transthoracic High-Resolution Ultrasound for Radiographically Undetected Rib Fractures (Journal of Fatima Jinnah Medical University, 2018)
Background: Blunt thoracic trauma comprises more than half of the rib fractures along with soft tissue injury. The sensitivity of conventional chest X-rays has been shown to be limited in showing rib fractures. Aims / Objectives: To determine the usefulness of transthoracic high resolution ultrasound in investigating the possible acute rib fractures which are overlooked on chest X-rays in minor blunt chest trauma. Material and Methods: This cross-sectional study was conducted in Department of Radiology, Omer Hospital, Lahore, between January and December 2010. A total of 28 adult subjects of either gender (25 male, 3 females; age range 18–65 years) were enrolled with minor blunt chest trauma, divided in two age groups; less than 40 years and above 40 years. The etiologies of trauma were: road traffic accident (n=13, 46.5%), direct trauma (n=7, 25%), fall (n=6, 21.4%) and sports injury (n=2, 7.1%). The site of the trauma was the right hemithorax in 11 (39.2%), left hemithorax in 8 (28.7%) and bilateral in 9 (32.1%) cases. Ecchymosis on the traumatized site was found in 5 (17.85%) patients only; although variable degree of tenderness was more frequently observed on the affected site of the chest wall. Preliminary chest radiograph showed no evidence of rib fracture. On follow up after 5 days, transthoracic ultrasound examination of most painful area with focal rib tenderness was examined. Results: A total of 23 (82.1%) patients demonstrated rib and chondral fractures on transthoracic ultrasound examination. There were 15 cases rib fracture (65.3%), 6 cases of chondral fracture (26%) and 2 cases of costochondral disruption (8.7%). An associated subperiosteal hematoma was found in 4 (17.4%) patients. The intensity and duration of pain in patients with bony rib fractures was significantly higher than that of patients with chondral rib fractures. Conclusion: Targeted high resolution ultrasound examination of chest wall should be performed as a more rewarding modality for the detection of occult rib and chondral fractures in the subjects having long standing chest wall pain after minor blunt trauma besides normal chest radiograph.
Keywords: Transthoracic ultrasound, high-resolution, rib fracture, blunt chest trauma.